CORRELATION BETWEEN VERTICAL DIMENSION OF OCCLUSION AND ANTHROPOMETRY OF FINGER LENGTH - Hasnaa Ramadhani Putri Pratami; Rahmad Arifin; Melisa Budipramana (Dentin, 2023)
ABSTRACTBackground: Determining the Vertical Dimension of Occlusion (VDO) was one of the procedures required to create a complete denture. VDO was the height of the lower third of the face that connected the distance between the subnation point found in the craniofacial and the gnation point on the mandible. The methods in determining VDO were very diverse, but there were no methods that considered as highly accurate presently. Hence, several methods of determining VDO were needed to obtain more accurate results. The finger length anthropometry method was a method that has been widely used as an alternative method in determining VDO because it was considered accurate, not invasive, cheap, and easy to implement. Objective: This study aimed to determine the correlation between the vertical dimensions of occlusion and the anthropometric length of fingers. Material and Method: The study was conducted by using the literature review method with the narrative review procedure. Research using Google Scholar, Science Direct, PubMed, and Semantic Scholar. Results: The results of the study of 22 articles reviewed had a positive correlation between VDO and all lengths of the fingers of the hand. The finger that had the strongest correlation with VDO in males was the index finger (r=0.804) and in females was the little finger (r=0.937) Conclusion: All fingers could be used as an alternative method in determining the Vertical Dimension of Occlusion.Keywords: Anthropometry, Finger length, Vertical Dimension of Occlusion